Quantitative analysis of histone demethylase probes using fluorescence polarization. - Xu, W; Podoll, J; Dong, X; Tumber, A; Oppermann, U; Wang, X (2013)
We previously reported methylstat as a selective inhibitor of jumonji C domain-containing histone demethylases (JHDMs). Herein, we describe the synthesis of a fluorescent analogue of methylstat and its application as a tracer in fluorescence polarization assays. Using this format, we have evaluated the binding affinities of several known JHDM probes, as well as the native cofactor and substrate of JHDM1A. This fluorophore allowed a highly robust and miniaturized competition assay sufficient for high-throughput screening.